LABOR DISCIPLINE ON THE EVE OF THE GREAT PATRIOTIC WAR (Bukhara region) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the strengthening of labor discipline throughout the country on the eve of the war (1940). Based on materials from periodicals, it was shown that measures against speculation and for the misappropriation of national, public and state property were also strengthened.